2003
DOI: 10.1097/00005537-200304000-00024
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Laser Vascular Targeting and Retinoic Acid in Oral Cancer Inhibition

Abstract: The study demonstrated the greater advantage of combining pulsed-dye laser with retinoic acid over using either retinoic acid or pulsed-dye laser alone for delay of oral cancer progression. Clinical trials are warranted to establish efficacy in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][10][11][12][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For several reasons the above assumption is not valid.…”
Section: Editormentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][10][11][12][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For several reasons the above assumption is not valid.…”
Section: Editormentioning
confidence: 99%
“…Tumor growth is dependent on angiogenesis for maintenance of an adequate blood supply 6 . Previous studies in our laboratory have demonstrated the effectiveness of the antiangiogenesis agent, retinoic acid (RA), in the chemoprevention of HNSCC 7,8 . It has a high incidence of side effects, however, which include dry skin, cheilitis, conjunctivitis, and hypertriglyceridemia 5 …”
Section: Introductionmentioning
confidence: 99%